Integrated Bioinformatics Analysis Reveals Key Candidate Genes and Pathways Associated With Clinical Outcome in Hepatocellular Carcinoma - Li, Yubin; Chen, Runzhe; Yang, Jian; Mo, Shaowei; Quek, Kelly; Kok, Chung H.; Cheng, Xiang-Dong; Tian, Saisai; Zhang, Weidong; Qin, Jiang-Jiang (Frontiers in Genetics, 2020)
Hepatocellular carcinoma (HCC) accounts for approximately 85%-90% of all liver cancer cases and has poor relapse-free survival. There are many gene expression studies that have been performed to elucidate the genetic landscape and driver pathways leading to HCC. However, existing studies have been limited by the sample size and thus the pathogenesis of HCC is still unclear. In this study, we performed an integrated characterization using four independent datasets including 320 HCC samples and 270 normal liver tissues to identify the candidate genes and pathways in the progression of HCC. A total of 89 consistent differentially expression genes (DEGs) were identified. Gene-set enrichment analysis revealed that these genes were significantly enriched for cellular response to zinc ion in biological progress group, collagen trimer in the cellular component group, extracellular matrix structural (ECM) constituent conferring tensile strength in the molecular function group, protein digestion and absorption, mineral absorption and ECM-receptor interaction. Network system biology